RARE CASE OF INFERIOR GLUTEAL ARTERY FALSE ANEURYSM FORMATION - A.D. GAIBOV; O. NEMATZODA; D.D. SULTANOV; N.R. KURBANOV; K.A. ABDUSAMADOV; Z.V. GAIBOVA (Avicenna Tajik State Medical University, 2017)
The article submitted a case of successful diagnostics and surgical treatment of a rare case of inferior gluteal artery false aneurysm formation due to the expressed retrograde blood flow. The probability of such a mechanism of aneurysm formation is possible in zones with rich collateral communications between the main vessels, and where there is a high retrograde pressure. The difficulties in the clinical diagnosis of aneurysm are described because of its inaccessibility for the study, as well as the weak pulsation of the aneurysmal sac and the absence of systolic thrill. This variant of an aneurysm was formed when, during the primary surgical intervention, the proximal end of the damaged vessel was ligated, and its distal end, having contracted, disappeared from the surgeon's field of vision. This led to the formation of an aneurysm 1.5 months after the injury. Aneurysmotomy performed and a suture was applied to a bleeding vessel participating in the formation of an aneurysm, with a good near and medium-distant result.